Prevalensi, Identifikasi Telur Trematoda dan Pengaruh Umur terhadap Trematodiasis pada Ternak Kambing di Kecamatan Sumbang Kabupaten Banyumas - Cattleya, Rania; Indrasanti, Diana; Yuwono, Endro (ANGON: Journal of Animal Science and Technology, 2024)
Background Background. One of the diseases that attack goats is intestinal worms which can cause a decrease in livestock productivity and receive less attention from breeders. This study aims to determine the prevalence of trematodiasis, the types of trematode eggs that are distributed, and to examine the effect of age on trematodiasis in goats in Sumbang District, Banyumas Regency. Methodology. The research material was in the form of 99 samples of goat feces with the age categories of kid (3-5 months), youth (6-12 months), and adults (> 12 months). The research methods used were surveys and laboratory tests so that the data obtained was in the form of interviews and the results of examining stool samples using the sedimentation method. Data analysis used is descriptive analysis and Chi-square analysis. Results. The prevalence of trematodiasis in goats in Sumbang District, Banyumas Regency was 32.32%. The type of trematode eggs found was Fasciola sp. (31.31%) and Paramphistomum sp. (1.01%). The results of the Chi-square analysis showed that there was a very significant difference indicating that age had a very significant effect on trematodiasis. Conclusion. The conclusion from the results of this study, the prevalence of trematodiasis in goats in Sumbang District, Banyumas Regency was relatively high with the results of identification of trematode eggs found to be Fasciola sp. and Paramphistomum sp., as well as the age factor of the livestock greatly influences trematodiasis.